Bayesian sparse‐based reconstruction in bioluminescence tomography improves localization accuracy and reduces computational time. Issue 4 (12th December 2017) - Feng, Jinchao; Jia, Kebin; Li, Zhe; Pogue, Brian W.; Yang, Mingjie; Wang, Yaqi
Abstract : Bioluminescence tomography (BLT) provides fundamental insight into biological processes in vivo. To fully realize its potential, it is important to develop image reconstruction algorithms that accurately visualize and quantify the bioluminescence signals taking advantage of limited boundary measurements. In this study, a new 2‐step reconstruction method for BLT is developed by taking advantage of the sparse a priori information of the light emission using multispectral measurements. The first step infers a wavelength‐dependent prior by using all multi‐wavelength measurements. The second step reconstructs the source distribution based on this developed prior. Simulation, phantom and in vivo results were performed to assess and compare the accuracy and the computational efficiency of this algorithm with conventional sparsity‐promoting BLT reconstruction algorithms, and results indicate that the position errors are reduced from a few millimeters down to submillimeter, and reconstruction time is reduced by 3 orders of magnitude in most cases, to just under a few seconds. The recovery of single objects and multiple (2 and 3) small objects is simulated, and the recovery of images of a mouse phantom and an experimental animal with an existing luminescent source in the abdomen is demonstrated. Matlab code is available athttps://github.com/jinchaofeng/code/tree/master . Abstract : The primary limitations of an application of bioluminescence tomography in preclinical studies are the inaccurate localization of sources and high computational cost. This article develops a new reconstruction algorithm by taking advantage of the sparsity and multispectral data. The algorithm can accurately recover source distribution in heterogeneous and complex tissues, while at the same time reducing the computation time in reasonable time limit.